Development of Mathematical Creative Inquiry Learning Model for secondary school mathematics learning - Abdul Hamid, Nor Haniza (2023)
Inspiring creativity through the curriculum is the result of ongoing efforts in the 21st century's educational development of worldwide change. As shown in the 2013-2025 National Education Blueprints, efforts are underway in Malaysia to improve the quality of the students' creativity. The purpose of this study is to develop the Mathematical Creative Inquiry Learning Model for secondary school mathematics learning. The development of the model is aimed to support formal learning in aiding students to achieve both learning needs and learning outcomes through mathematical creative inquiry learning activities. The study applies the Design and Development Research (DDR) approach, and the research is implemented in three phases; needs analysis, design and development, and evaluation. Phase 1 utilized the needs analysis using a survey questionnaire involving 120 secondary school Mathematics teachers to determine the need to develop the Mathematical Creative Inquiry Learning Model. Phase 2 obtained the views of 12 experts through the Nominal Group Technique (NGT) and the Interpretive Structural Modeling (ISM) method to design and develop the model. The evaluation phase included the use of the Fuzzy Delphi method (FDM), which involves 25 Mathematics teachers to evaluate the model. The threshold value (d) is determined to establish the consensus of the experts for all the arrangement of the learning elements. The findings in Phase 1 revealed that the mathematics teachers agreed with all items regarding their views on creativity in mathematics learning (Mean = 4.42, SD = 0.691). The results also concluded that the mathematics teachers showed a high positive agreement on their views of all the creative learning elements in Mathematics based on the person (Mean = 4.35, SD = 0.774), process (Mean = 4.36, SD = 0.733), product (Mean = 4.28, SD = 0.848), and press (Mean = 4.26, SD = 0.845) perspectives. The overall findings for Phase 1 indicated a high acceptance among Mathematics teachers to use the Mathematical Creative Inquiry Learning Model in their formal Mathematics syllabus (Mean = 4.52, SD = 0.608) and the need to develop the model. Findings from Phase 2 resulted in the model's design and development, consisting of 27 creative inquiry learning activities determined by a panel of experts. The experts also viewed that the activities could be grouped into six learning domains and four learning clusters to interpret the representation of the learning activities. Finally, the findings from Phase 3 showed consensus agreement between the experts in terms of the arrangement of the learning activities, the suitability of the main domains, the cluster classification of the learning activities, and the overall evaluation of the model. The threshold value, d for all the items in this phase, is less than 0.2 and has more than 75 percent consensus between the experts. The model proposes how the mathematical creative inquiry learning activities could be incorporated into formal Mathematics learning to achieve the learning outcomes. Additionally, the research results may guide mathematics educators to integrate creativity inquiry learning activities among secondary school students.